Comparison of Employer Productivity Metrics to Lost Productivity Estimated by Commonly Used Questionnaires. Issue 2 (February 2016) - Gardner, Bethany T.; Dale, Ann Marie; Buckner-Petty, Skye; Van Dillen, Linda; Amick, Benjamin C.; Evanoff, Bradley
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: The aim of the study was to assess construct and discriminant validity of four health-related work productivity loss questionnaires in relation to employer productivity metrics, and to describe variation in economic estimates of productivity loss provided by the questionnaires in healthy workers. Methods: Fifty-eight billing office workers completed surveys including health information and four productivity loss questionnaires. Employer productivity metrics and work hours were also obtained. Results: Productivity loss questionnaires were weakly to moderately correlated with employer productivity metrics. Workers with more health complaints reported greater health-related productivity loss than healthier workers, but showed no loss on employer productivity metrics. Economic estimates of productivity loss showed wide variation among questionnaires, yet no loss of actual productivity. Conclusions: Additional studies are needed comparing questionnaires with objective measures in larger samples and other industries, to improve measurement methods for health-related productivity loss.